An organic programmable diode with pentacene, zinc oxide nanoparticles and polymethylsilsesquioxane - Lee, W.K.; Wong, H.Y.; Aw, K.C. (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
In this paper, we proposed an organic programmable diode as a memory device. This device consists of layers of pentacene and zinc oxide nanoparticles embedded in polymethylsilsesquioxane. The device exhibits a change in current flow of an order up to 10(5) and is comparable or better to many reported organic diode memory devices. A two-barrier model has been used to explain the memory effect of the organic diode. The device can be written and erased multiple times similar to a flash memory. (C) 2011 Elsevier Ltd. All rights reserved.